Gambaran Status Gizi Berdasarkan Berat Badan /Umur, Tinggi Badan/Umur Dan Lingkar Kepala Tahun 2022 - Roslina Gumilar; Siti Soviah; Lia Yuliyani (Jurnal Obstretika Scientia, 2023)
Nutritional status is the state of the body as a result of the interaction between energy and protein intake. As well as other essential nutrients with the state of health of the body. Nutritional status is the condition of the body as a result of the absorption of essential nutrients. Nutritional status is an expression of the balance of nutrients with body needs, which is realized in the form of certain variables. The purpose of this study was to determine the description of nutritional status based on BB / U, TB / U and LK in infants in the work area of the Insani Kopo Clinic, Seranf Regency in 2022. This type of research is descriptive research conducted in the work area of the Insani Clinic with a sample of 46 people. Nutritional status data were collected by taking anthropometric measurements. Data were analyzed univariately. The results showed that the nutritional status based on BB / U category of good nutritional status was 69.2%, the category of nutritional status was less than 26.4% and the category of nutritional status was very less than 4.4%. Based on TB/U, the normal nutritional status category was 63.6%, the short nutritional status category was 23.9%, and the very short nutritional status category was 12.5%. Based on BB/TB, the category of good nutritional status was 85.9% and the category of poor nutritional status was 14.1%. It is recommended for the work area of Klinik Insani Kopo kab. serang to provide nutrition education to baby mothers so that babies can grow and develop properly